ANALYSIS OF VARIABLES IN THE SELECTION OF TRANSPORTATION MODES FOR STUDENTS OF SMA NEGERI 1 KUTACANE FOR THE 2023/2024 ACADEMIC YEAR - Taufik Taufik (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
Transportation is a need in the community including students in reaching school, students can use various modes of transportation such as private or public transportation, education creates a need for transportation to school. Therefore, the author is interested in conducting research aimed at identifying the choice of modes between private and public transportation in students for the 2023/2024 school year. SMA Negeri 1 Kutacane was chosen as a case study in the research. The research methodology used in this is a revealed preference approach with a cross-tabulation analysis method (cross tab). Based on data collection, it was found that personal transportation is the most widely used mode of transportation by students of SMA Negeri 1 Kutacane to go to school. Based on the variables studied, there are several variables that have a significant relationship with the type of transportation mode chosen. Overall, variables that have a significant relationship with the choice of mode of transportation are Allowance (X4), How to Depart (X6), and Cost (X9).